Persepsi Mahasiswa Pendidikan Teknik Bangunan Jurusan Teknik Sipil FT-UNP Terhadap Kesempatan Kerja Sebagai Guru - Hartika Srinita; Rijal Abdullah (Teknik Sipil Universitas Negeri Padang, 2020)
This study aims to determine the perceptions of Building Engineering Education students on job opportunities as teachers. The population in this study were students of the Building Engineering Education Study Program who were taking their thesis in the July-December 2020 semester totaling 70 students and a sample of 40 students. The research data was carried out through a questionnaire given to students who were the research samples to determine student perceptions of job opportunities as teachers using the Likert scale. Based on the research that has been carried out, it can be concluded that the results of the study indicate that the students' perceptions of building engineering education on job opportunities as teachers were 79.72%, the category was quite good. So it can be concluded that Building Engineering Education students who are taking their thesis July-December 2020 semester have a pretty good perception of job opportunities as teachers.